PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MUATAN PELAJARAN ILMU PENGETAHUAN SOSIAL MATERI JENIS-JENIS USAHA MASYARAKAT INDONESIA KELAS V SDS EKA TJIPTA KENCANA - Fajar Septyawan (CV Putra Publisher, 2023)
Learning and teaching are essentially a reciprocal relationship between teachers and learners. The use of media and learning methods chosen by teachers is one way to improve the quality of learning. Problem Based Learning is an innovation in learning because in PBL students' thinking skills are really optimized through a systematic group or team work process, so that students can empower, hone, test and develop their thinking skills on an ongoing basis. This study used Classroom Action Research. Data is obtained through data collection in the field which is carried out using observation techniques, learning outcome test techniques, and documentation. From the results of the analysis, the results were obtained that after the implementation of the Problem Based Learning learning model, there was an increase in teacher activity, an increase in student activity and an increase in student learning outcomes. From the results of the research conducted, it is suggested that SDS Eka Tjipta Kencana teachers can use the Problem Based Learning learning model as an alternative learning to improve student learning outcomes